Romatoid Artritli hastalarda aortik sertleşme - Masatlıoğlu, Seval; Ayaydın, Semiha; Demirtunç, Refik; Yılmaz, Güven; Yolcu, Nilcihan; Kayataş, Kadir; Duman, Dursun (My University, 2011)
Romatoid Artirit (RA) de mortalitenin en önemli sebebi kardiyovasküler sistem (KVS) tutulumudur. Aortun mekanik özelliklerinin invaziv olmayan yöntemlerle değerlendirilmesi aterosk-lerozun erken tanısında oldukça yararlıdır. Bu çalışmada; ateroskleroz gelişimine yol açabilecek başka hastalığı ve risk faktörleri olmayan RA'lı hastalarda aortun elastisite parametreleri ile hastalığın aktivite ölçümleri arasında etkileşim olup olmadığı araştırılmıştır. Yöntem: Çalışmaya 46 RA'li hasta ve 20 sağlıklı birey alındı. Hastaların hastalık süresi, DAS-28 skorları, eritrosit sedimentasyon hızı (ESH), C-reaktif proteinleri (CRP) ve lipid düzeyleri kaydedildi. Ekokardiyografik değerlendirme ile aortun elastik parametreleri hesaplandı ve gruplar arasında karşılaştırma yapıldı. RA'lı hastaların aktivite ölçümleri ile aortun elastik parametreleri arasındaki ilişki araştırıldı. Bulgular: RA'lı hastaların aortik strain ve distensibilite düzeyi; kontrol grubuna göre daha düşük bulundu (p<0.002). Aortik strain ile ESH arasında istatistiksel olarak ileri düzeyde anlamlı bir ilişki saptanmıştır (p<0.01). Distensibilite ile DAS28 ve ESH arasında istatistiksel olarak anlamlı bir ilişki bulundu (p<0.05). Sonuç: Ekokardiyografi ile noninvaziv metod olarak ölçülen aortik elastisite parametreleri hastalığın erken döneminde kardiyovasküler riski tahmin etmede faydalı olabilir.

In patients with RA, the cardiovascular system involvement is the most important reason for the increase of mortality. Evaluation by non-invasive methods of mechanical properties of the aorta is quite useful in early diagnosis of atherosclerosis. In this study we have investigated that the relation between aortic elasticity parameters and the disease activity criteria in the RA patients who has not have any risk factors and any diseases leading to the development of atherosclerosis. Method: 46 RA patients and 20 healthy subjects were included in the study. The patients, disease duration and DAS-28 scores and ESR and CRP and lipid parametres results were recorded. Echocardiographic evaluation was performed and the aortic elastic parameters were calculated and compared between groups. Activity parameters of patients with RA and the relation between aortic elastic parameters were investigated. Results: Aortic strain and distensibilitiy levels of RA patients, were lower than the control group (p <0.002). According to there is no statistically significant difference between patient and control groups. There is a statistically significant relationship between DAS28 and distensibilitiy (p <0.05). And there is a statistically significant correlation between ESH and distensibility (p <0.01). And there is advanced level of statistically significant correlation between strain and the ESH (p <0.01). Conclusion: Aortic elasticity parameters measured by echocardiography as a noninvasive method may be useful to predict the risk of cardiovascular disease at early stages.
Aortic stifness in patients with rheumatoid Arthritis
Keywords: Romatoid Artrit; Ateroskleroz; Aort Sertliğİ; Aort Distensibilite; Rheumatoid Arthritis; Aortic Strain; Aortic Distensibility